Social determinants of depression and suicidal behaviour in the Caribbean: a systematic review - Catherine R Brown; Ian R Hambleton; Natasha Sobers-Grannum; Shawn M Hercules; Nigel Unwin; E Nigel Harris; Rainford Wilks; Marlene MacLeish; Louis Sullivan; Madhuvanti M Murphy; The U.S. Caribbean Alliance for Health Disparities Research Group (USCAHDR) (BMC, 2017)
Abstract Background Depressive disorder is the largest contributor to years lived with disability in the Caribbean, adding 948 per 100,000 in 2013. Depression is also a major risk factor for suicidal behaviour. Social inequalities influence the occurrence of depression, yet little is known about the social inequalities of this condition in the Caribbean. In support of the 2011 Rio Political Declaration on addressing health inequities, this article presents a systematic review of the role of social determinants on depression and its suicidal behaviours in the Caribbean. Methods Eight databases were searched for observational studies reporting associations between social determinants and depression frequency, severity, or outcomes. Based on the PROGRESS-plus checklist, we considered 9 social determinant groups (of 15 endpoints) for 6 depression endpoints, totalling 90 possible ways ('relationship groups') to explore the role of social determinants on depression. Studies with ≥50 participants conducted in Caribbean territories between 2004 and 2014 were eligible. The review was conducted according to STROBE and PRISMA guidelines. Results were planned as a narrative synthesis, with meta-analysis if possible. Results From 3951 citations, 55 articles from 45 studies were included. Most were classified as serious risk of bias. Fifty-seven relationship groups were reported by the 55 included articles, leaving 33 relationship groups (37%) without an evidence base. Most associations were reported for gender, age, residence, marital status, and education. Depression, its severity, and its outcomes were more common among females (except suicide which was more common among males), early and middle adolescents (among youth), and those with lower levels of education. Marriage emerged as both a risk and protective factor for depression score and prevalence, while several inequality relationships in Haiti were in contrast to typical trends. Conclusion The risk of bias and few numbers of studies within relationship groups restricted the synthesis of Caribbean evidence on social inequalities of depression. Along with more research focusing on regional social inequalities, attempts at standardizing reporting guidelines for observational studies of inequality and studies examining depression is necessitated. This review offers as a benchmark to prioritize future research into the social determinants of depression frequency and outcomes in the Caribbean.